2013
DOI: 10.1111/jce.12116
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Sphericity: A New Method to Assess Atrial Remodeling. Impact on the Outcome of Atrial Fibrillation Ablation

Abstract: Left Atrial Sphericity is a new independent predictor of recurrence after AF ablation and may be useful in selecting the best candidates for AF ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
175
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(192 citation statements)
references
References 36 publications
12
175
4
Order By: Relevance
“…This is despite the limitation of using a solitary linear measurement to characterize a three-dimensional shape [22]. Furthermore, recent data suggest that atrial remodeling not only leads to enlargement but also distinct symmetry changes as well [21,23,24]. Recently, it has been demonstrated that LA size-, morphology-, and volume are better predictors of AF recurrence after LA ablation than anterior-posterior LA diameter measurements [23][24][25].…”
Section: Prediction Of Pulmonary Vein Isolation Successmentioning
confidence: 92%
“…This is despite the limitation of using a solitary linear measurement to characterize a three-dimensional shape [22]. Furthermore, recent data suggest that atrial remodeling not only leads to enlargement but also distinct symmetry changes as well [21,23,24]. Recently, it has been demonstrated that LA size-, morphology-, and volume are better predictors of AF recurrence after LA ablation than anterior-posterior LA diameter measurements [23][24][25].…”
Section: Prediction Of Pulmonary Vein Isolation Successmentioning
confidence: 92%
“…The original motivation was to obtain a smooth parametrizations from a triangulations of star-shaped surfaces in R 3 representing the left atrium of the heart of a sample of patients with atrial fibrillation, see [2].…”
Section: Introductionmentioning
confidence: 99%
“…The trans-axial images were acquired with a slice thickness of 0. 5 and reconstructed with a voxel size of 0.5 × 0.4 × 0.4 3 . The protocol of this study was approved by the local research ethics committee.…”
Section: Data Preparationmentioning
confidence: 99%
“…Previous studies reported that hypertension, Holter duration, left atrial (LA) volume and LA sphericity [2,3,4,5] were potentially related to post-ablation recurrence, but their underlying mechanism is still unclear, as is LA remodeling in AF.…”
Section: Introductionmentioning
confidence: 99%